Changes in nutritional content in raw milk of the Simmental breed cows fed with different forage combinations - Beyaz, Baki; Demİr, Ersin; Erİşİr, Figen Erdem; Temİzer, İbrahim Akın; Yilmaz, Ökkeş (Refik Saydam National Public Health Agency (RSNPHA), 2024)
Objective: In this study, the biochemical compositions of fatty acids, amino acids, fat-soluble v'tamins (ADEK), cholesterol and phytosterols were examined in raw milk samples of Simmental breed cows fed with different forage combinations. Methods: Milk samples were prov'ded from their farm in Kovancılar district of Elazığ province in Türkiye. The cows were fed in different forage combinations the spring season. These were Group 1: cows fed with Beet pulp+Factory feed+Hay (n: 10); Group 2: cows fed with Maize silage+Barley+Hay (n: 10), and Group 3: cows free-fed in pasture (n: 10). Milk samples were taken on the 15th day of feeding and brought to the laboratory. Biochemical analyses were performed on the milk samples brought to the laboratory in accordance with the cold chain rules. After the milk samples went through a number of biochemical processes, fatty acid, ADEK v'tamins, cholesterol and amino acid analyses were performed. The analysis of cholesterol and ADEK vitamins was performed with a high performance liquid chromatography (HPLC) dev'ce, and analysis of amino acids and fatty acids was performed with gas chromatography (GC) and FID detector. Results: 18 amino acids were detected in the milk samples examined. Compared to Group 1, it was found that the amounts of arginine (p<0.001), isolosine (p<0.05), methionine (p<0.05), threonine (p<0.05), phenylalanine (p<0.001), lysine (p<0.05) and tryptophan (p<0.001) amino acids increased statistically, while the amounts of alanine (p<0.001), glycine (p<0.05), leucine (p<0.05), aspartic acid (p<0.01) and glutamic acid (p<0.05) decreased statistically in Group 3. Compared to Group 1, it was found that the amounts of arginine (p<0.001), threonine (p<0.05), phenylalanine (p<0.001) and lysine (p<0.05) amino acids increased statistically, while the amounts of alanine (p<0.001), glycine (p<0.001), proline (p<0.01), aspartic acid (p<0.05), glutamic acid (p<0.001), histidine (p<0.001) and tryptophan (p<0.05) decreased statistically in Group 2. Compared to Group 1, the amounts of lauric acid (p<0.05), myristic acid (p<0.01), pentadecanoic acid (p<0.05), palmitic acid (p<0.01), stearic acid (p<0.001), oleic acid (p<0.001) and cholesterol (p<0.05) were statistically decreased, while the amounts of linoleic acid (p<0.001), alpha-linolenic acid (p<0.001), dihomo-gamma-linolenic acid (p<0.05), vitamin K2 (p<0.001), ?—tocopherol (p<0.001), vitamin D2 (p<0.001), a-tocopherol (p<0.001), ?-tocopherol acetate (p<0.05), vitamin K1 (p<0.001), stigmasterol (p<0.01), B-sitosterol (p<0.05) were statistically increased in Group 3. Compared to Group 1, the amounts of stearic acid (p<0.001), oleic acid (p<0.01), a-tocopherol acetate (p<0.001) and B-sitosterol (p<0.05) were statistically decreased, while the amounts of vitamin K2 (p<0.001), Y-tocopherol (p<0.01), vitamin D2 (p<0.01), a-tocopherol (p<0.01), vitamin K1 (p<0.01) and stigmasterol (p<0.01) were statistically increased in Group 2. It was determined that the amounts of palmitic, oleic, myristic, stearic, lauric, linoleic, palmitoleic and pentadecanoic acids were found to be above 1% in the fatty acid composition of milk among the groups, respectively. It was determined that there were significant changes in the amount of some fatty acids among the groups. In addition, it was determined that there were significant changes in the amounts of cholesterol, phytosterol and some ADEK v'tamins among the groups. Conclusion: According to these data, it is seen that the use of different feed combinations in animal nutrition by dairy producers is very important for enriching the biochemical content of milk. It has been determined that the nutrient content of milk changes depending on different feed combinations and feeding in the flora. In addition, it has been found that the milk content of cows fed in pasture is more significantly enriched with nutrients necessary for a healthy life. © (2024), (Refik Saydam National Public Health Agency (RSNPHA)). All Rights Reserved.
Farklı yem kombinasyonları ile beslenen Simmental ırkı ineklerin çiğ sütünde besin içeriğindeki değişiklikler
Keywords: Amino acids; Aminoasitler; chemical composition; dairy biochemistry; kimyasal bileşim; lipids; lipitler; raw milk; süt biyokimyası; vitaminler; vitamins; çiğ süt